2019
DOI: 10.1353/hpu.2019.0082
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction of the Primary Care, Mental Health, and Dental Health Clinicians of the National Health Service Corps Loan Repayment Program

Abstract: T he quality of any clinician's work life affects matters far beyond that clinician's personal happiness. This is true for clinicians serving in the National Health Service Corps (NHSC), who provide care to socioeconomically challenged patients in chronically understaffed clinics and under-resourced communities. Like all clinicians, those in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…We presented findings for clinicians in 3 broad fields, which may overlook important differences among disciplines within each field. 77 Twenty-five clinicians (1.3% of all respondents) completed NHSC service contracts before the survey and had since relocated and reported on their experiences in new practices, which may be better than where they worked in the NHSC and which they had elected to promptly leave.…”
Section: Discussionmentioning
confidence: 99%
“…We presented findings for clinicians in 3 broad fields, which may overlook important differences among disciplines within each field. 77 Twenty-five clinicians (1.3% of all respondents) completed NHSC service contracts before the survey and had since relocated and reported on their experiences in new practices, which may be better than where they worked in the NHSC and which they had elected to promptly leave.…”
Section: Discussionmentioning
confidence: 99%
“…Two publications described providers' perceptions of and experiences with the NHSC and found that behavioral health providers reported being satisfied with most facets of the NHSC program but few reported being satisfied with their wages and workloads. One 2019 study revealed that over 85% of surveyed behavioral health providers indicated that they applied to the NHSC LRP for educational debt assistance and over 70% indicated they did so to help the underserved (35). The vast majority of behavioral health providers reported being satisfied with their NHSC LRP experiences, work, practices, and communities and these findings were comparable to responses by other non-behavioral health NHSC LRP participants (35).…”
Section: Providers' Perceptions Of and Experiences With The Nhsc (K=2)mentioning
confidence: 99%
“…One 2019 study revealed that over 85% of surveyed behavioral health providers indicated that they applied to the NHSC LRP for educational debt assistance and over 70% indicated they did so to help the underserved (35). The vast majority of behavioral health providers reported being satisfied with their NHSC LRP experiences, work, practices, and communities and these findings were comparable to responses by other non-behavioral health NHSC LRP participants (35). However, fewer than half of behavioral health providers were satisfied with their compensation or time demands at work.…”
Section: Providers' Perceptions Of and Experiences With The Nhsc (K=2)mentioning
confidence: 99%
“…14 Other factors such as lifestyle, family considerations, financial incentives, practice characteristics, availability of loan forgiveness, and personal characteristics also influence the decision to practice in rural areas. 15 These factors are multifaceted, nuanced, and interrelated, and studies investigating the relative influence of these various factors on rural practice are lacking.…”
Section: Introductionmentioning
confidence: 99%